2022
DOI: 10.1007/s13668-022-00397-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Assessment of Nutrition Knowledge in Athletes

Abstract: Purpose of Review Adequate nutrition knowledge may influence dietary behaviour, and the performance and health of athletes. Assessment of the nutrition knowledge of athletes can inform practice and provide a quantitative way to evaluate education interventions. This article aims to review nutrition knowledge questionnaires published in the last 5 years to identify advances, possible improvements in questionnaire development and design, and challenges that remain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Educational studies have been criticized for using a wide range of knowledge assessment tools with limited validation, which makes it difficult to compare results across studies [32,75]. In the present study, we developed twenty statements specifically relevant for female endurance athletes with a risk of RED-S that were suitable for a short telephone interview, so that participants were not able to find the answers in books or on the internet which they could have done with an online distributed questionnaire.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational studies have been criticized for using a wide range of knowledge assessment tools with limited validation, which makes it difficult to compare results across studies [32,75]. In the present study, we developed twenty statements specifically relevant for female endurance athletes with a risk of RED-S that were suitable for a short telephone interview, so that participants were not able to find the answers in books or on the internet which they could have done with an online distributed questionnaire.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In the present study, we developed twenty statements specifically relevant for female endurance athletes with a risk of RED-S that were suitable for a short telephone interview, so that participants were not able to find the answers in books or on the internet which they could have done with an online distributed questionnaire. Our knowledge tool is an abbreviated version of what has been used in previous studies [32,69,75]. Consequently, scores may not be fully representative of sports nutrition knowledge and direct comparisons with other studies are not possible.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In this study, based on the correct response of the nutrition knowledge and practice score, the study participants demonstrated a relatively low level of nutrition knowledge and practice compared to previous findings where less than half had poor nutritional knowledge ( 16 , 43 , 44 ). The optimum nutrition knowledge is crucial for fostering athletic performance in athletes, which further shows that increasing nutrition knowledge is related to dietary intake and subsequent sports performance ( 10 , 45 ). In addition, systematic review has shown that athletes who obtain nutrition education might become more understanding about nutrition, which will optimize their dietary intake ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…As established within the literature, adequate nutrition is paramount for performance, recovery, and adaptation to training, along with optimising the maturation process during adolescence [96,103,125]; thus, sufficient nutritional knowledge is required to optimise dietary behaviours to support these processes and inform eating habits [126][127][128][129][130][131]. In the absence of sufficient nutritional knowledge, nutritional intake may be compromised due to poor food selection and decreased dietary quality [132].…”
Section: Nutrition Knowledge Of Adolescentsmentioning
confidence: 99%